8 - Developing or Managing the Poor: The Complexities and Contradictions of Free Basic Electricity in South Africa (2000-2006) - Ruiters, Greg (Africa Development, 2021)
The new South African government since 2001 developed what might be called a skeletal welfare system that extends social grants, infrastructure and free services to millions of previously deprived citizens. Extending electricity is held up as a major developmental intervention. A free amount of household electricity has been provided specifically to improve the lives of the poor and of women, but also to fortify a payment ethic for services in a country where grassroots, anti-apartheid organizations had long boycotted payments and where citizens expected the African National Congress to provide services for free. However, in the last five years, spiralling illegalities and non-payment have undermined service delivery. Some argue that the current rollout of services is unsustainable when large numbers of people are unemployed and cannot afford the services. The state walks a tightrope between helping without encouraging dependency, providing access yet setting limits, and encouraging entrepreneurialism and household ‘good governance’. Located within critical social policy debates, the aim of the paper is to outline, evaluate and analyse the complex process of managing services and managing the poor. I use the prism of the South African government’s innovative, free basic electricity (FBE) programme to explore the tensions between helping and controlling the poor, and we explore what this might reveal about the class functions of the South African state. I focus on the tensions within policy, and the gaps between policy intentions and techniques of implementation. I examine the content of the FBE policy, its everyday social technologies and underlying managerial rationales, and problems of protests and illegal access. Although offering a degree of temporary relief for very poor households, FBE re-inscribes social exclusion, and with the procedures of indigent means te ting, discourages the poor from seeking access and trusting the state.